Memberdayakan Kesadaran Toleransi di Masyarakat Muslim - Farida, Farida (Community Development: Jurnal Pengembangan Masyarakat Islam, 2019)
Empowering Tolerance Awareness in Muslim Communities. This study aims to investigate empowering awareness of tolerance in Muslim communities. This research is a type of library research, namely, by recording all findings and combining all findings, both theory and new findings, both from books, websites, articles and newspapers about the role of civil society in the midst of a pandemic, analyzing all findings from various readings. and provide critical ideas about empowering tolerance awareness in Muslim societies. The results of the study show that tolerance awareness is accustomed to starting from the family, at school and in the community by fostering a sense of happiness and pride in being a Muslim human being in a Muslim society. Simultaneous habituation of tolerance awareness makes individuals ready to accept change and social adaptation. If this becomes a shared responsibility, empowerment of tolerance awareness can be carried out to live in harmony in Indonesia, where the majority of the people are Muslims.